In Vitro Antibakteri Ekstrak Etanol Puni (Zingiber zerumbet) Asal Pulau Timor - Origenes Boy Kapitan; Laksmi Ambarsari; Syamsul Falah (Savana Cendana, 2017)
Puni (Zingiber zerumbet) is a wildly grown plant that used by Timorese people to treat ulcerative lesions in Timor Island. This study aims to determine the antibacterial activity of plants extracts and know the content of active compounds on the most active extracts of plants. Extraction of active compounds was carried out using four solvent ie n-hexane, ethyl acetate, ethanol, and aqueous solvent. Antibacterial activity test was done using the diffusion method of the four crude extract and extract with the highest activity was then used to find MIC value. Analyzed the content of the active compounds using LC-MS. It was found that ethanol extract had the highest antibacterial activity compared to other extracts. The MIC value of ethanol extract against S. aureus, B. Subtilis, E. coli, and P. aeruginosa were respectively determined to be 50, 100, 150, 250 mg mL-1. The result of LC-MS analysis showed that the ethanol extract contained zerumbone and gingerglycolipid B.